Short term memory, physical fitness, and serum brain-derived neurotrophic factor in obese adolescents - Rini Rossanti; Dida Akhmad Gurnida; Eddy Fadlyana (Paediatrica Indonesiana, 2015)
Background Obesity in adolescents is a major health problem and has been associated with low academic achievement. Brainderived neurotrophic factor (BDNF), a neurotrophin, plays a role in appetite suppression and memory, and its secretion is enhanced by physical activity. This neurotrophin may be associated with academic achievement in obese. Objective To compare physical fitness and serum BDNF levels to short term memory levels in obese adolescents aged 10–14 years. Methods This comparative, cross-sectional, analytic study was carried out on 40 elementary and high school students in Bandung, West Java, who were recruited by stratified random sampling. Short term memory was assessed by a psychologist using the Wechsler Intelligence Scale for Children-III Digit Span test (WISC-III Digit Span). Physical fitness was assessed by a clinical exercise physiologist using the Asian Committee on the Standardization of Physical Fitness Test (ACSPFT). Serum BDNF levels were measured by ELISA test in a certified laboratory. ANOVA test was used to assess for a correlation between serum BDNF concentration and short term memory, as well as between physical fitness level and short term memory. Pearson’s correlation test was used to analyze for a correlation between serum BDNF and physical fitness levels. Results The majority of subjects were in the physical fitness categories of moderate or poor. Subjects had a mean BDNF level of 44,227.8 (SD 10,359) pg/mL. There was no statistically significant difference in physical fitness with either serum BDNF or with short term memory levels (P=0.139 and P=0.383, respectively). Also, no correlation was determined between serum BDNF and physical fitness levels (r=0.222; P=0.169). Conclusion In obese adolescents, short term memory levels are not significantly different between physical fitness levels nor between serum BDNF levels.